Policy Options for Meeting the Millennium Development Goals in Brazil : Can Micro-Simulations Help? - Ferreira, Francisco H.G.; Leite, Phillippe George (World Bank, Washington, DC, 2014)
The authors investigate whether micro-simulation techniques can shed light on the types of policies that should be adopted by countries wishing to meet their Millennium Development Goals. They compare two families of micro-simulations. The first family of micro-simulations decomposes required poverty changes into a change in the mean and a reduction in inequality. Although it highlights the importance of inequality reduction, it appears to be too general to be of much use for policymaking. The second family of micro-simulations is based on a richer model of behavior in the labor markets. It points to the importance of combining different policy options, such as educational expansion and targeted conditional redistribution schemes, to ensure that the poorest people in society are successfully reached. But the absence of market equilibria in these statistical models, as well as the strong stability assumptions which are implicit in their use, argue for extreme caution in their interpretation.